2019
DOI: 10.1161/cir.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Device Therapy and Arrhythmia Management in Left Ventricular Assist Device Recipients: A Scientific Statement From the American Heart Association

Abstract: Left ventricular assist devices (LVADs) are an increasingly used strategy for the management of patients with advanced heart failure with reduced ejection fraction. Although these devices effectively improve survival, atrial and ventricular arrhythmias are common, predispose these patients to additional risk, and complicate patient management. However, there is no consensus on best practices for the medical management of these arrhythmias or on the optimal timing for procedural interventions in patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 168 publications
0
144
0
3
Order By: Relevance
“…A recent statement from the AHA in which a review of the literature was performed found the short-term success of VA ablation in a predominantly CF-LVAD cohort ranging from 77% to 86%, and variable VA recurrence at follow-up, ranging from 15% to 85%. 38 Moss et al reported an increased incidence of pump thrombosis following ablation in CF-LVAD patients, especially when ablation was performed adjacent to the inflow cannula. 14 However, larger prospective trials are needed to draw any conclusions about the risk of pump thrombosis and other complications associated with ablation in patients with CF-LVADs.…”
Section: Cf-lvad Implantationmentioning
confidence: 99%
“…A recent statement from the AHA in which a review of the literature was performed found the short-term success of VA ablation in a predominantly CF-LVAD cohort ranging from 77% to 86%, and variable VA recurrence at follow-up, ranging from 15% to 85%. 38 Moss et al reported an increased incidence of pump thrombosis following ablation in CF-LVAD patients, especially when ablation was performed adjacent to the inflow cannula. 14 However, larger prospective trials are needed to draw any conclusions about the risk of pump thrombosis and other complications associated with ablation in patients with CF-LVADs.…”
Section: Cf-lvad Implantationmentioning
confidence: 99%
“…Arrhythmias are common in patients with LVADs. The mechanisms behind arrhythmias in this patient populations are complex, however, they pertain to abnormal myocardium before LVAD implantation as well as ventricular remodeling therafter 26 . As it has been established that implantable cardioverter‐defibrillators (ICDs) improve survival in patients with both ischemic (and potentially non‐ischemic) cardiomyopathy, most patients who are considered for LVAD candidacy already have an ICD 27,28 .…”
Section: Etiologies Of Shock In Patients With Lvadsmentioning
confidence: 99%
“…As it has been established that implantable cardioverter‐defibrillators (ICDs) improve survival in patients with both ischemic (and potentially non‐ischemic) cardiomyopathy, most patients who are considered for LVAD candidacy already have an ICD 27,28 . The frequency of ventricular arrhythmias decrease as the patient becomes further removed from their LVAD implantation 26 …”
Section: Etiologies Of Shock In Patients With Lvadsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 The burden of ventricular arrhythmias is high in these patients, with observational studies suggesting that as many as 20%–50% of patients experience ventricular arrhythmias after LVAD implantation. 2 , 3 Mechanisms of arrhythmogenesis include physical contact between the inflow cannula and myocardium, myocardial scar, and electrolyte disturbances. Ventricular tachycardia (VT) can be difficult to manage medically, and catheter ablation is often necessary.…”
Section: Introductionmentioning
confidence: 99%